Rhionaeschna caligo revisited: female and larval descriptions, new geographical records and natural history notes (Odonata: Aeshnidae) - Arango-Quintero, Sebastian; Sánchez, Isabel Cardona; González, Wilmar Zapata; Bota-Sierra, Cornelio A. (Zootaxa, 2025)
The species Rhionaeschna caligo Bota-Sierra, 2014, endemic to the páramos of the northwestern Central Cordillera of the Colombian Andes, was described in 2014 based on eight males. Females, larvae, and many aspects of this species’ natural history were previously unknown. This article presents the results of three expeditions carried out in 2024 to the Belmira páramo complex (Antioquia, Colombia), providing the first description of the female and last instar larva of R. caligo. In addition, a new distribution record is included, accompanied by photographs and natural history notes that complement the information on its ecology and behavior.